2012
DOI: 10.1186/1471-2415-12-32
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of DSAEK interface with scanning-laser confocal microscopy

Abstract: BackgroundDescemet Stripping Automated Endothelial Keratoplasty (DSAEK) allows selective replacement of the endothelium. Post-operative haze and particles can affect the interface quality and, ultimately, visual outcome. In this study, we evaluated DSAEK interface with in vivo laser confocal microscopy (LCM) in order to: (i) correlate interface status with best corrected visual acuity, and (ii) with time from surgery; (iii) correlate interface particle number with best corrected visual acuity. Host-donor inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…47, 48 With repeated prospective images and analyses, we quantified the change in reflectivity and optical quality of regions of interest with time after surgery. Various other methods (confocal microscopy, scatterometry, and Scheimpflug cameras) 9, 11, 13 have been used to assess scatter post-DSAEK. Confocal microscopy utilizes a point illumination light source and a pinhole to minimize out-of-focus signal.…”
Section: Discussionmentioning
confidence: 99%
“…47, 48 With repeated prospective images and analyses, we quantified the change in reflectivity and optical quality of regions of interest with time after surgery. Various other methods (confocal microscopy, scatterometry, and Scheimpflug cameras) 9, 11, 13 have been used to assess scatter post-DSAEK. Confocal microscopy utilizes a point illumination light source and a pinhole to minimize out-of-focus signal.…”
Section: Discussionmentioning
confidence: 99%
“…[25] This finding is in contrast with what was found in a study from Italy that revealed a good quality interface is related to a better visual acuity and improves with time from surgery. [26]…”
Section: Discussionmentioning
confidence: 99%
“…Also donor-recipient interface haze has been assumed to affect visual outcome after endothelial keratoplasty [ 13 , 37 , 38 ]; in contrast Espana et al [ 30 ] and Baratz et al [ 23 ] did not find a significant correlation between interface reflectivity and visual outcome. Our data show a correlation between interface haze and postoperative BCVA at 3 and 6 month follow-up, whereas considering the interval changes interface haze reduction positively affected BCVA at 6-to-12 months only.…”
Section: Discussionmentioning
confidence: 99%